THE EFFECT OF SELF EFFICACY AND MOTIVATION ON ENTREPRENEURSHIP INTERESTS IN BUSINESS ADMINISTRATION STUDENTS - Yusnidar; Cut Sukmawati; Nursakinah Ritonga; Nanda Ameliany; Lisa Iryani (RADJA PUBLIKA, 2025)
Economic problems are the main concern of the government in developing countries, for example, such as Indonesia unemployment and poverty. One solution to dealing with unemployment is to become an entrepreneur and create jobs for oneself and others, namely by entrepreneurship. And this can be realized if equipped with supporting knowledge, namely entrepreneurship. This research aims to determine the influence of self-efficacy and motivation variables on interest in entrepreneurship in Business Administration students at FISIPOL UNIMAL. This research used 100 samples with a sampling technique, namely non-probability sampling. The data were analyzed using multiple linear analysis with the help of the IBM SPSS 25.0 program. The results of the research show that partially the self-efficacy variable is positive and significant on interest in entrepreneurship among FISIPOL UNIMAL Business Administration students. This can be seen from the significant value of the self-efficacy variable, namely sig. is 0.000 < 0.05 and the tcount value is 6.056 > ttable 1.985, then H1 is accepted. For the motivation variable, it was concluded that it partially had a positive and significant effect on interest in entrepreneurship among FISIPOL UNIMAL Business Administration students. This can be seen from the significant value of the motivation variable, namely sig. is 0.000 > 0.05 and the t value is 5.001 > t table 1.985, then H2 is accepted. Meanwhile, simultaneously the variables self-efficacy and motivation together have a positive and significant effect on interest in entrepreneurship among FISIPOL UNIMAL Business Administration students.